Cognitive Function Profile of Post-Stroke Patients - Dila Larasati; Irma Ruslina Defi; Henny Anggraini Sadeli (International Journal of Integrated Health Sciences, 2017)
Objective: To discover cognitive function profile of post-stroke patients undergoing rehabilitation to inform rehabilitation professionals in planning for a program and provide services that meet the patient’s need. Methods: This study was a descriptive cross-sectional study involving 32 post-stroke patients undergoing rehabilitation at the Physical Medicine and Rehabilitation clinic of Dr. Hasan Sadikin General Hospital Bandung in August–September 2014. An examination was conducted using the Mini Mental State Examination (MMSE) to obtain the cognitive function profile of post-stroke patients. Results: The results showed that almost all post-stroke patients undergoing rehabilitation had normal cognitive functions (93.8%), only few patients had probable cognitive impairment (6.2%). Probable cognitive impairment were found in male and female patients who were in the age range of 50–60 years who were elementary school graduates and in the sub acute phase of stroke. Conclusions: Almost all post-stroke patients undergoing rehabilitation have normal cognitive functions, only minority of patients have probable cognitive impairment, and there are no patients with definite cognitive impairment. Keywords: Cognitive function, education, rehabilitation, stroke DOI: 10.15850/ijihs.v5n1.962